Exploring TPACK domains of Malaysian non-option ESL teachers in an online flipped learning course through Blendspace - Mohd Faisal Farish bin Ishak; Abdul Ghani Abu (Universitas Islam Sultan Agung, 2018)
The purpose of this paper is to explore teachers’ Technological Pedagogical and Content Knowledge (TPACK) domains in planning digital tools-based activities. It discusses a small part of a major study that investigated Malaysian non-option ESL teacher’s flipped ESL instructional design of teaching and learning in their own classroom context. Participants were involved in this case study. The miniscule analysis was done for a digital tool called Blendspace (a learning management system – LMS) in order to investigate teacher’s classroom activity plans. The digital tools introduced to the participants were meant to support their ESL flipped learning instructional design. Findings show that new input ameliorated the existing TK domain and made it developmental. This has resulted an improvised TPACK which I coined a term ‘Augmented TPACK’ – an inclusive TPACK domains that consists of developmental TK and non-developmental PK and CK. Participants used Augmented TPACK to plan digital tools-based activity.